PENGARUH ROTASI KERJA, MOTIVASI KERJA DAN SEMANGAT KERJA TERHADAP KINERJA PEGAWAI KOMISI INDEPENDEN PEMILIHAN (KIP) ACEH - Saifuddin, Saifuddin; Kamaruddin, Kamaruddin (IndOmera, 2021)
The purpose of this study is to prove and analyze, 1). The effect of job rotation on employee performance, 2) The effect of work motivation on employee performance, 3) The influence of employee morale on employee performance, and 4). Effect of job rotation, work motivation. and Simultaneous morale on the performance of Aceh KIP employees. The analysis was carried out descriptively and with a Path Analysis approach. The results of this descriptive study showed that the response of KIP Aceh employees who were examined regarding work rotation, found that the implementation of work rotation that could make high employee performance was only achieved by 59.67%. Likewise, regarding employee work motivation, both with the support of employee needs, as well as the achievement of motivation expected by employees in the Aceh KIP environment only reached 68.82% which is classified as good. And the work spirit of Aceh KIP employees, the achievements tend to be good reaching 71.07%. The results of the path analysis prove that 1) there is a significant effect on employee performance by 16.67%, 2) there is a significant influence on work motivation on the performance of Aceh KIP employees, which is 11.94%. 3) There is a significant effect of work morale on the performance of Aceh KIP employees, amounting to 23.45%. and 4). There is a simultaneous influence of work rotation, work motivation and work spirit on the performance of Aceh KIP employees by 52.8%. While the remaining 47.2% not researched, such as work facilities, compensation, career development, education, and others